Desain Pendidikan Karakter dalam Membentuk Kepedulian Sosial di Pesantren - Zubaidi, Ahmad (TSAQOFAH, 2022)
The purpose of this study was to determine the design of character education in forming social awareness in Islamic boarding schools. The method used in this study was a qualitative research with a phenomenological approach. Data collection techniques were carried out by interviews, observations and documentation. Data analysis techniques are carried out by means of data reduction, data presentation, and drawing conclusions. While checking the validity of the data was carried out by extending the time and persistence of observations, triagulation techniques and discussions with seniors. The findings of the research are as follows: (1) The design of character education for the social care of students at the Nurul Jadid Islamic Boarding School runs naturally by maintaining the traditions of the pesantren which lead to the formation of the character of the social care of students. (2) Efforts to form the social care character of the students include: (a) The formation of the character of the social care of the students through organizational culture. (b) Formation of the character of social care for students through kiai figures (c) Formation of character for social care through alumni (d) Formation of the character of social care for students through books and lessons.